Validation of the Malay Version of the COVID-19 Anxiety Scale in Malaysia - Ang, Chin Siang; Lee, Kai Wei; Ho, Meng Chuan; Voon, Siok Ping; Ching, Siew Mooi *; Tan, Chai Eng; Hoo, Fan Kee; Ooi, Pei Boon * (Penerbit Universiti Sains Malaysia, 2022)
Background: Malaysians are disillusioned with the increased number of COVID-19 infection cases and the prolonged lockdown period. As a result of COVID-19 mitigation measurements, Malaysians are experiencing emotional and psychological consequences such as anxiety. Thus, there is an urgent need to have an instrument that could serve as a tool to assess the psychological impact of COVID-19 among Malaysians rapidly.